2012 4th Computer Science and Electronic Engineering Conference (CEEC) 2012
DOI: 10.1109/ceec.2012.6375393
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of channel error upon selectively encrypted H.264 video

Abstract: Abstract-For real-time video streaming applications it is important to preserve both privacy and delay sensitivity. To achieve, this selective encryption exploits the entropy coding stage of hybrid codecs. As streaming applications move towards mobile networks, they become vulnerable to bit errors in the wireless channel. This paper is a pioneering analysis of the relative impact of bit errors on the two H.264 codec entropy coders, CAVLC and CABAC. The joint impact of compression and encryption on objective vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The selective encryption on MVDs and TCs keeps the video format compliant (playable) and without escalating bit rates. As previously discussed in the research of [24], H.264/AVC's CAVLC is more susceptible to channel errors as compared to CABAC. Thus, this paper devised a protection scheme for the H.264-CABAC entropy coder, which can be applied to HEVC compression, with a few comparatively minor modifications.…”
Section: Compression and Privacy Protectionmentioning
confidence: 87%
See 2 more Smart Citations
“…The selective encryption on MVDs and TCs keeps the video format compliant (playable) and without escalating bit rates. As previously discussed in the research of [24], H.264/AVC's CAVLC is more susceptible to channel errors as compared to CABAC. Thus, this paper devised a protection scheme for the H.264-CABAC entropy coder, which can be applied to HEVC compression, with a few comparatively minor modifications.…”
Section: Compression and Privacy Protectionmentioning
confidence: 87%
“…In [24], the authors examined the comparative effects of channel errors on selectively encrypted video bitstreams by two H.264 codec entropy coders Context Adaptive Binary Arithmetic Coding (CABAC) and Context Adaptive Variable Length Coding (CAVLC). They determined the combined effect of compression and encryption on the video quality and concluded that CAVLC is more susceptible to channel error.…”
Section: Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of noise on the proposed scheme was already examined by us in [5]. In that paper, it was concluded that CAVLC coding is significantly more sensitive to channel bit errors than CABAC.…”
Section: Effect Of Noise Contaminationmentioning
confidence: 93%
“…In both these methods, the decoder bitstream remains format compliant. Other work by us has confirmed the resistance to perceptual attacks [25] and examined to what extent the core SE technique can tolerate errors in a wireless channel [26].…”
Section: Introductionmentioning
confidence: 99%